Implementasi Manajemen Koridor Ekologi Taman Nasional Gunung Halimun Salak - Marningot Tua Natalis Situmorang; Tatan Sukwika; Tanjung Prasetyo (Dinamika Lingkungan Indonesia, 2024)
Habitat fragmentation in ecological corridors is a threat to preserving habitat and animals. Habitat is vital as a corridor to support animal mobility and migration patterns in preventing meta-population. The 1 km long Luewiliang Bogor currently threatens the habitat of the Mount Halimun Salak corridor – Cipeutey Sukabumi road access. This research examines endemic animals, flagship spesies, and conservation category animals in their habitat. The corridor area of this research location, reaches 20 km2 in Cianten village, Bogor Regency. Line transect, camera trap, integrated remote sensing methods are methods used to monitor animal movements. This research consists of animal inventory research on the distribution of endemic and threatened animals and research into motor vehicle disturbance. From the observations and research carried out, seven mammal species were obtained, namely: Deer (Muntiacus muntjak), Coconut Squirrel (Callosciurus notatus), Javan Gibbon (Hylobates moloch), Root Civet (Arctogalidia trivirgata), Surili (Presbyris comata), Leopard (Panthera pardus), Mouse Deer (Tragulus napu) and 6 types of birds, namely: Prenjak Bird (orthomus sp), Liitle Honey Bird (Anthrepetes simplex), Butbut Bird (Centrpus sinensis), Javanese Eagle (Spezaitus bartelsi), Brotok Eagle (Nisaetus cirrhatus) and Tuluk Tumpuk Bird (Psilopogon javensis). Motorized vehicles average 15 vehicles/hour. Transportation type; trucks, buses, cars, motorbikes.